JEFFERSON AND TOCQUEVILLE ON DEMOCRACY AS HEMISPERIC VIEWS - Didik Murwantono (Rubikon : Journal of Transnational American Studies, 2014)
This paper examines democracy to Jefferson’s and Tocqueville’s philosophy in shaping the American polity. A few scholars have discussed the connection between Jefferson and Tocqueville, but this writing provides a value of democracy as hemispheric mind or trans-national sources. Democracy is not only an American intellectual mind, but also a global mind. The philosophers, sociologists, and economists of the eighteenth and the early part of the nineteenth century formulated a political program that served as a guide to social policy first in the United States, then on the European continent, and finally in the other parts of the inhabited world as well. It was reflected in Tocqueville’s journey for learning democracy in America around the mid of the nineteenth century. Therefore, there are two significant points to describe both Tocqueville and Jefferson; they are democracy and tradition with all conditions.